Pengaruh Promosi Dan Citra Merek Terhadap Keputusan Pembelian Pada Alfamart Tiban Ciptaland Batam - Fenny Novianti; Tiurniari Purba (JURNAL EKUIVALENSI, 2022)
ABSTRACT This study aims to determine the effect of promotion on purchasing decisions at Alfamart Tiban Ciptaland Batam, the influence of brand image on purchasing decisions at Alfamart Tiban Citaland Batam. This study uses a quantitative design. By using a research sample of 140 respondents who are consumers who have made purchases at Alfamart Tiban Ciptaland. Data collection techniques in this study have been tested for validity and reliability. The data analysis technique used is multiple regression analysis. This study has the result that the Promotion variable has a positive and significant effect on purchasing decisions at Alfamart Tiban Ciptaland Batam. This can be proven from the calculated t value which is 12,529 with a significance value of 0.000 which is smaller than 0.05 (0.000 <0.05); and the brand image variable has a positive and significant effect on purchasing decisions at Alfamart Tiban Ciptaland Batam. This statement is obtained based on the t-count value which is 7.528 with a significance value of 0.000 which is smaller than 0.05 (0.000<0.05); Promotion and brand image have a positive and significant effect on purchasing decisions at Alamart Tiban Ciptaland Batam, this statement is obtained from the calculated f value which is 209.338 with a significance value of 0.000 which is smaller than 0.05 (0.000 <0.05).